2021
DOI: 10.1007/s00330-021-08391-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the field of view (FOV) on image quality in MDCT angiography of the lower extremities

Abstract: Objectives To evaluate the impact of the reconstructed field-of-view (FOV) on image quality in computed-tomography angiography (CTA) of the lower extremities. Methods A total of 100 CTA examinations of the lower extremities were acquired on a 2 × 192-slice multidetector CT (MDCT) scanner. Three different datasets were reconstructed covering both legs (standard FOV size) as well as each leg separately (reduced FOV size). The subjective image quality was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Smaller FOVs of CT images are usually associated with clearer images and higher resolution [12] . As reported that a small FOV reconstruction in CT angiography of lower extremities signi cantly improved image quality compared with a large FOV reconstruction covering two legs [13] . In order to explore a better approach to present pulmonary nodules.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Smaller FOVs of CT images are usually associated with clearer images and higher resolution [12] . As reported that a small FOV reconstruction in CT angiography of lower extremities signi cantly improved image quality compared with a large FOV reconstruction covering two legs [13] . In order to explore a better approach to present pulmonary nodules.…”
Section: Discussionmentioning
confidence: 95%
“…On the premise of maintaining diagnostic performance and refusing excessive radiation, the small-eld-of-view reconstruction CT images (sFOV-CT) increased pixel density across airway structures and reduced partial volume effects [8] . As is well-known that the decrease of reconstructed FOV has a bene cial impact on image quality using both subjective and objective measures [9] . The sFOV reconstruction approach via reducing FOV has been widely studied in the diffusing-weighted sequence in prostate cancer [10] , rectal carcinoma [11] , and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller FOVs in CT images are often associated with clearer and higher resolution images 12 . Studies have reported that a small FOV reconstruction in CT angiography of the lower extremities significantly improved image quality compared to a large FOV reconstruction covering two legs 9 . In order to explore a better approach to presenting pulmonary nodules, we applied an sFOV reconstruction algorithm to c-CT images and compared their difference statistically.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sFOV in CT are proved to be associated with higher spatial resolution and clearer images after subjective evaluation by radiologists. It has been demonstrated that reducing the reconstructed field of view (FOV) has a beneficial impact on increasing diagnostic image quality in CTA run-off examinations, regardless of vessel size 9 . Furthermore, a smaller and adjusted FOV or an increased matrix was well established to improve the spatial resolution in other part of body in CT 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to increase the image quality and diagnostic accuracy include optimization of acquisition parameters (10)(11)(12) and optimization of reconstruction parameters, including the use of innovative reconstruction algorithms beyond filtered back projection (FBP) (2,13). In addition to these algorithms, it is also possible to improve the image quality and spatial resolution by reducing the reconstruction field of view (FOV) with side-separate reconstruction of the legs, which results in sharper images (14). Another approach to improve the spatial resolution and sharpness of structures is to increase the size of the reconstruction matrix (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%